2020
DOI: 10.5114/ada.2020.102103
|View full text |Cite
|
Sign up to set email alerts
|

Serum level of interleukin-15 in active alopecia areata patients and its relation to age, sex, and disease severity

Abstract: Introduction Autoimmune mechanisms with evident genetic background are the main components of alopecia areata (AA) pathogenesis. Interleukin 15 (IL-15) is considered as an important signalling cytokine. Its disordered expression has been linked to inflammatory autoimmune disorders. Aim The present study aimed to evaluate serum IL-15 in active AA patients and to assess its association with patients’ sex, age, and disease severity. Material and methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
2
2
0
Order By: Relevance
“…This was found to be true, in contrast to [15], who did not find a significant difference between the serum levels of patients and the healthy control group. The IL15 serum levels are significantly greater in the ill group than in the control group (P= 0.001), according to the findings of the earlier studies [16] and these findings were consistent with those of the current investigation. A recent study [12] that found that serum levels of IL-15 were significantly higher in patients with AA and revealed a strong positive link with the severity and activity of the disease supports the findings of this investigation.…”
Section: Resultssupporting
confidence: 92%
“…This was found to be true, in contrast to [15], who did not find a significant difference between the serum levels of patients and the healthy control group. The IL15 serum levels are significantly greater in the ill group than in the control group (P= 0.001), according to the findings of the earlier studies [16] and these findings were consistent with those of the current investigation. A recent study [12] that found that serum levels of IL-15 were significantly higher in patients with AA and revealed a strong positive link with the severity and activity of the disease supports the findings of this investigation.…”
Section: Resultssupporting
confidence: 92%
“…These results agreed with those of Ragab et al's study in 2020 [ 13 ]. Aşkın et al's study in 2021 [ 14 ] and Salem et al's study in 2019 [ 15 ] concluded that the level of IL-15 with AA were significantly higher in the case of control groups ( P < 0.001).…”
Section: Discussionsupporting
confidence: 93%
“…Even though autoimmune diseases are generally related to the gender of patients, no gender ascendancy is seen in AA ( P =0.9). Likewise, it has been shown that there was no association between IL-15 level and patients age, ( P =0.14), recurrence of disease, or history of AA in the same family of the patient ( P > 0.05) [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…This in turn may lead to activation of autoreactive CD8 + T cells via presentation of HF autoantigens, represented potentially by trichohyalin peptides (33) and other autoantigens, by MHC class I molecules (39). IFN-g also stimulates the production of IL-2 and IL-15; activated CD8 + T cells stimulated by IL-15 further mediate IFN-g secretion via the JAK/ signal transducer and activator of transcription (STAT) pathway (36), specifically through JAK1/JAK3 signaling (79,80).…”
Section: Ifn-g-il-15 Positive Feedback Loop and The Jak/stat Pathway ...mentioning
confidence: 99%